Swida australis as a resource species of Dagestan - F. M. Suleimanova; Z. M. Asadulaev; A. B. Izmailov (Юг России: экология, развитие, 2025)
Aim. Study of the variability of the biochemical composition of fatty oils from the pericarp and seeds of Swida australis depending on the altitudinal conditions of growth of natural populations for assessment as a resource species in the field of medicine.Fruits of S. australis were selected along the altitudinal gradients: 15 m, 620 m and 1000 m. The method of circulation extraction in a Soxhlet extractor using a volatile extractant – n-hexane was used to extract lipids. Comparative quantitative assessment was carried out by the Folch method. After determining the oil yield, one part of it was used to find the triglyceride composition by reversed-phase high-performance liquid chromatography, the second, was converted into methyl esters to determine the acid composition of lipids by chromatograph mass spectrometry. The quality of the oil was assessed by determining the acid number and saponification number. A correlation assessment of the content of triacylglycerides, hydrocarbons and biologically active compounds (polyunsaturated fatty acids) with the altitudinal level of growth is given based on the Pearson method at a reliability level of  p < 0.05.For the first time, the component composition of lipids isolated from the pericarp and seeds of S. australis was studied and the resource potential for medicine was assessed. The oil obtained is characterised by a high content of triacylglycerides, hydrocarbons and biologically active compounds and - in particular - polyunsaturated fatty acids, which are used in medicine.Analysis of oil isolated from the pericarp and seeds of S. australis showed a high content of triacylglycerides, hydrocarbons and biologically active compounds (polyunsaturated fatty acids). It is proposed to initially extract all lipids using the Folch method, followed by hexane extraction of triacylglycerides and hydrocarbons in order to separate them from valuable biologically active substances.